Investigation of CO2 and H2O Addition to Natural Gas for Production of Synthesis Gas (Iranian Journal of Chemical Engineering)
General modeling and optimization of syngas production via noncatalytic autothermal partial oxidation of methane are carried out using our developed scientific software which was based on the minimization of total Gibbs energy. In this work, a novel application of the direct search and Newton-Raphson methods was introduced to apply to optimization of a complex chemical reaction. Sensitivity analysis was done to investigate the effect of several parameters on the quality of syngas and the production yield. The acceptable concentrations of CO2 and H2O injected into the methane feed are optimized in the specified temperature and pressure range, while H2/CO ratio in the product stream is set to remain at 1.5 or 2, methane slip in the syngas is less than 1.5% and the non-endothermic conversion area of reaction prevail, simultaneously. This facilitates monetizing CO2 in the petrochemical and steel industries. The output from this software is comparable both with the experimental results, cited in Ref [1] , and with that from ASPEN PLUS in simulating the experiments mentioned in Ref [2]